Thermal and Sound Insulation Properties of Recycled Expanded Polystyrene Granule and Gypsum Composites - Girts Bumanis; Pauls Pavils Argalis; Genadijs Sahmenko; Deniss Mironovs; Sandris Rucevskis; Aleksandrs Korjakins; Diana Bajare (Recycling, 2023)
Up to now, primary resources have been the main choice of raw material selection for production. Now, global market tendencies have brought significant attention to secondary resources as the price has been raised for primary materials, and there is a shortage of their delivery. This could bring an additional effort to increase the recycling level of construction and demolition waste, including expanded polystyrene (EPS). Efforts have been made to develop new efficient building materials with a high content of recycled EPS. In this paper, composite insulation material made of gypsum hemihydrate and recycled EPS beads by casting and compression methods were evaluated, and properties were compared. Thermal and sound insulation properties were characterized. Density from 48 to 793 kg/m3 was obtained and the thermal conductivity coefficient from 0.039 to 0.246 W/(m·K) was measured. Compression strength was from 18 kPa to 2.5 MPa. Composites produced with the compression method have a sound absorption coefficient α > 0.9 in the range from 600 to 700 Hz, while the samples produced by casting showed poor sound absorption with wide deviation. Compression methods had an advantage over the casting method as more homogenous and lightweight materials were produced with improved insulation properties.